Constructing 'the Best Interests of the Child' in Digital Space Governance: A Critical Discourse Analysis of Government Regulation No. 17 of 2025 - Atef Fahrudin (Jurnal Komputer, Informasi dan Teknologi, 2026)
This study aims to examine how the concept of "the best interests of the child" is constructed in Indonesia's Government Regulation No. 17 of 2025 concerning Electronic System Governance for Child Protection, and to identify the digital child protection paradigm embedded within this regulatory framework. The method employed is Norman Fairclough's Critical Discourse Analysis, examining the regulation through three dimensions: textual analysis of lexicon, grammar, and modality; discursive practice analysis of production, consumption, and intertextuality; and social practice analysis of power relations and underlying ideologies. The results reveal that "the best interests of the child" is operationalized through three fundamental dimensions: normative prioritization placing children's rights above commercial interests (Article 8b), age-appropriate design mechanisms with five granular age categories (Article 20), and privacy by design approach shifting from reactive to anticipatory protection (Articles 2, 10). The regulation constructs a hybrid paternalistic-participatory paradigm, mandating parental consent while providing children limited agency through reporting mechanisms (Articles 9, 23). Notably, it prohibits profiling and deceptive design, fundamentally challenging surveillance capitalism's business model. State-centric governance with stringent corporate accountability characterizes the power relations, adopting UK's Age-Appropriate Design Code principles with contextual adaptations. The conclusion indicates that PP 17/2025 successfully translates abstract principles into enforceable technical obligations, positioning Indonesia within global regulatory convergence while maintaining local contextualization, though implementation challenges remain regarding digital literacy gaps, cross-border enforcement, age verification mechanisms, and cultural pluralism considerations.